Additions to the knowledge of the genus Parancistrocerus Bequaert, 1925 from China (Hymenoptera: Vespidae: Eumeninae) - Qin, Jiong; Chen, Bin; Li, Ting-Jing (Zootaxa, 2023)
In this paper, three new species, namely Parancistrocerus fragilitergus sp. n. from Guangxi (China), P. elatitergus sp. n. from Sichuan (China), and P. extentitergus sp. n. from Chongqing and Guizhou (China) are described and illustrated in detail. In addition, P. irritatus Giordani Soika, 1972, P. jaferpaloti Girish Kumar & Carpenter, 2016, and P. sulcatus Giordani Soika, 1994 are newly recorded from China. An updated key to the Chinese species of the genus Parancistrocerus is provided.